Who is the Historian? The Formation of Modern Greek History and the Historical Community in the Short Twentieth Century - Karamanolakis, Vangelis (Historein, 2021)
The position of historian emerged as a distinct academic and professional field in Greece in the last quarter of the 20th century. In an attempt to explore this “delay” in comparison to Western European countries, this article offers an overview of the making of the field of modern Greek history during the twentieth century. Starting from the gradual acknowledgment of the autonomy of modern Greek history in relation to classical and Byzantine studies, the article traces its evolution and its close ties to political and social developments. The prevalence of historical positivism and philological principles, along with the dominance of the ideology of national continuity – the latter enriched through the postwar ideologies of national-mindedness and anticommunism – led to the persistence of the “historian-philologist” until 1974. The fall of the military dictatorship in 1974, which marked the end of the post-Greek Civil War era, was a catalyst for the flowering of modern Greek studies and the formation of a small but distinct community of historians, who regularly intervened in the public sphere.